Case Report: Compound Heterozygous Variants in MOCS3 Identified in a Chinese Infant With Molybdenum Cofactor Deficiency - Tian, Qi; Cao, Yang; Shu, Li; Chen, Yongjun; Peng, Ying; Wang, Yaqin; Chen, Yuanyuan; Wang, Hua; Mao, Xiao (Frontiers in Genetics, 2021)
Background: The molybdenum cofactor (Moco) deficiency in humans results in the inactivity of molybdenum-dependent enzymes and is caused by pathogenic variants in MOCS1 (Molybdenum cofactor synthesis 1), MOCS2 (Molybdenum cofactor synthesis 2), and GPHN (Gephyrin). These genes along with MOCS3 (Molybdenum cofactor synthesis 3) are involved in Moco biosynthesis and providing cofactors to Moco-dependent enzymes. Until now, there was no study to confirm that MOCS3 is a causative gene of Moco deficiency. Methods: Detailed clinical information was collected in the pedigree. The Whole-exome sequencing (WES) accompanied with Sanger sequencing validation were performed. Results: We described the clinical presentations of an infant, born to a non-consanguineous healthy family, diagnosed as having MOCS3 variants caused Moco deficiency and showing typical features of Moco deficiency including severe neurologic symptoms and cystic encephalomalacia in the brain MRI, resulting in neonatal death. Compound heterozygous variants in the MOCS3 gene were identified by WES. Positive sulfite and decreased levels of uric acid in plasma and urine were detected. Conclusion: To our knowledge, this is the first case of MOCS3 variants causing Moco deficiency. Our study may contribute to genetic diagnosis of Moco deficiency and future genetic counseling.